Efficiency and risk in European banking - Fiordelisi, Franco; Marques-Ibanez, David; Molyneux, Phil (Journal of Banking & Finance, 2011)
We assess the inter-temporal relationship between bank efficiency, capital and risk in a sample of European commercial banks employing several definitions of efficiency, risk and capital and using the Granger-causality methodology in a panel data framework. Our results suggest that lower bank efficiency with respect to costs and revenues Granger-causes higher bank risk and that increases in bank capital precede cost efficiency improvements. We also find that more efficient banks eventually become better capitalized and that higher capital levels tend to have a positive effect on efficiency levels. These results are generally confirmed by a series of robustness tests. The results have potentially important implications for bank prudential supervision and underline the importance of attaining long-term efficiency gains to support financial stability objectives.